Az EU klímavédelmi törekvései, különös tekintettel az Európa 2020 stratégiára és Párizsra - Szamek, Gabriella (Közép-Európai Közlemények, 2017)
The combat against the climate change began with the United Nations Framework Convention on Climate Change (1992) and with the Kyoto Protocol (1997) on the field of law. This area was and has been since controversial, because the efforts to decrease the emission are in the way of the economic interest. At the same time it’s an especially dynamic territory. The climate protection, and the fight against the climate change is present in the primary and secondary EU Law as well. In my essay I present the EU law, and the case law of the Court of Justice of the Europian Union. The Europe 2020 strategy has an influence on the climate protection goals of the EU, therefore it gets a special attention, nevertheless, in this analysis I’ll focus on the aspects which are relevant to climate change. The Paris Agreement is the latest and the most important international convention in the cooperation against climate change. In my study I’m pointing out the shortcomings and achievements of the Agreement.